Socio-Economic Characteristics of Agelat, Libya - AFIFI, HANI; EL-SHAHAT, MAHMOUD; FRIZELL, JOHN; EL-WIFATI, BASHIR (The Libyan Journal of Agriculture, 2023)
Relatively little information hasexisted in Libya concerning the socio-economic aspects of rural people. The object of this study was to determine the socio-economic characteristics of the rural population of Agelat in Libya. A questionnaire was prepared and interviews undertaken in Summer 1969. The economy of Agelat has been, and is mainly based on agriculture. Farm sizes are small, half of the farms having a size of less than ten hectares. Farmers expressed the need for technical information. Most of these farmers are uneducated and this forms an obstacle to any attempt to transform traditional agriculture to a developed one. Educating the young people is the only hope for Libyan agriculture to reach its optimum efficiency. Every farmer has a radio, therefore radio programs should be designed to help the farmers in solving their problems.